Application of Multigrid for the Solution of Compressible Reynolds Equation of Gas Foil Bearings - Xu, Kefan; Zhang, Guanghui; Han, Jiazhen; Gong, Wenjie; Huang, Yanzhong; Guo, Yang (Tribology transactions, 2023)
The multigrid algorithm can reduce the iterative residuals quickly, but it is rarely used in research about gas foil bearings. This article adopts the Reynolds equation as the pressure governing equation of bump-type foil journal bearings to study the effect of different numerical methods on the execution time of the algorithm program, including the direct method, the iterative method, and the multigrid algorithm. The results indicate that the algorithm performs best, based on the nonlinear discretization scheme and multigrid, and the execution time is generally reduced by 50% compared to the traditional direct method under the same operating parameters. For the case of a large eccentricity ratio, the execution time can even be reduced by up to 68%. The multigrid algorithm is greatly affected by the cycle type parameter and the level numbers of the grid. V-cycle and larger grid-level numbers are recommended on the premise of program convergence. In summary, the multigrid algorithm is an excellent numerical solution that can balance computational accuracy and efficiency when solving the gas lubrication problem of foil bearings.